DAMPAK REGULASI PEMERINTAH,TEKNOLOGI INFORMASI DAN PRAKTIK SERVICE SUPPLY CHAIN MANAGEMENT TERHADAP KINERJA OPERASI (Studi Pada Televisi Lokal Di Jawa Timur) - ZAINAL ABIDIN ; Armanu T, Djumilah Hadiwidjojo,Surachman (Disertasi Manajemen FEB - UB, 2018)
The objective of this study is to analyze and review the influence of goverment regulations and information technology on the operational performance of local television stations in East Java with service supply chain management practices as the mediator variable and capital owner?s intervention as the moderator variable. The data of explanatory research was collected through questionaires distributed to twenty-nine local televisions stations, selected through saturated sampling method from a population of local television stations in East Java, and was analyzed using structural equation modeling. The finding of this study reveal that goverment regulations and information technology significantly influence the operational performance of local television stations with service supply chain management (SCM) practices as the mediator variable, wich means that better government regulations and better information technology are analogous with the important for the improvement of local television stations operational performance. Capital owner intervention weakens service SCM practices on operating performance and has a direct an immediate effect on on reducing the operational performance of local television stations. The practical implications of this study signifies the understanding that service SCM practices is an important concept in enhancing the operational performance. Capital owner?s intervention weakens service SCM practices on operating performance of local television stations. The limitation of this study is that government regulations on content control, have not included government regulations on network stations. The analysis of this study is based on surveys in the presentation of relationship analysis in a certain period. Since the existence of the stations is dynamics, further studies that assess the changes in the linkages among variables analyzed in this study are needed, Keywords: local television stations, government regulations, information technology, service supply chain management practices, operational performance, capital owner?s intervention